O uso do farelinho de arroz na alimentação dos animais - Braga, J F (Revista Ceres, 1939)
1- This article summarizes a large part of the existing literature relative to the use of rice bran in livestock reations and also includes a brief report of rice production in the United States and Brasil as well as comments on milling processes. 2—Rice bran, when fed alone, or in large amounts with protein supplement, produces soft pork. 3—Rice bran is more valuable than ground corn for fatten- ing hogs when the two are fed alone as single feeds. 4—When fed with protein supplement rice bran has 90% ol the value of corn for fattening pigs weighing 60 pounds or more. 5—Finishing fattening hogs with rice bran and corn in the ratio 1:1, was not sufficient to harden the fat, when the first ration was principally rice bran. 6—The ration of rice bran alone or supplemented with pro- tein, was unpalatable and bulky when used for hogs. 7—Rice bran can constitute from 50 to 60% of the ration with ground corn and 10% tankage without the produc- tion of soft fat. 8—Rice bran compared with whaet bran for feeding milk cows gives better results than wheat bran. 9—Experiments indicate that rice bran is about 75 to 80% as efficient as ground corn for dairy cattle. 10—The rice bran did not injure the flavor of whole milk even when fed in large quantities. 11—To prevent the rice bran from becoming rancid the man- ufacture of pressed cake was suggested. It was also suggested that rice bran may be heated to 105°C. for 3 hours and kept in a moisture preof container. 12—The rice bran has the most nutritive part of the rice grain. 13—The proteins of rice bran have a high biological value and compare favorably with meat proteins. 14—Rice bran is not an important feed for sheep. 15—Rice bran may be used for sheep without ill effects but it does not produce the cheapest gains. 16—Rice bran is not an important feed lor hor: and mules. However it may be used as one part of the ra- tion. 17—Rice bran is good feed for poultry when used as a part of the ration. 18—The use of 6 to 10% of rice bran in the ration, prevents peroses. 19— Sterilizing rice bran destroys the peroses — preventing factor. 20—Much more information is needed in order to use rice bran for livestock to the best advantage.